LUCIFER - a NIR spectrograph and imager for the LBT - Mandel, H; Appenzeller, I; Bomans, D; Eisenhauer, F; Grimm, B; Herbst, T; Hofman, R; Lehmitz, M; Lemke, R; Lehnert, M; Leneen, R; Luks, T; et al. (2000)
LUCIFER (LBT NIR-Spectroscopic Utility with Camera and Integral-Field Unit for Extragalactic Research) is a full cryogenic NIR spectrograph and imager (lambda 0.9 mu - 2.5 mu, zJHK-bands) to be built by a consortium of five institutes (Landessternwarte Heidelberg (LSW), Max Planck Institut fur Astronomie in Heidelberg (MPIA), Max Planck Institut fur Extraterrestrische Physik (MPE) in Garching, Astronomisches Institut der Ruhr Universitat Bochum (AIRUB) and Fachhochschule fur Technik und Gestaltung (FHTG) in Mannheim). The instrument has been selected as one of three first-light instruments for the Large Binocular Telescope (LBT) on Mt. Graham, Arizona which first mirror becomes available to the community in early 2003. The second mirror and a second more or less identical spectrograph/imager follows 18 month later. Both LUCIFER instruments will be mounted at the bent Gregorian foci of the two individual LET-mirrors and include six observing modes: seeing and diffraction limited imaging, seeing and diffraction Limited longslit spectroscopy, seeing limited multi-object spectroscopy (MOS) and integral-field spectroscopy (IFU). The detector will be a Rockwell HAWAII-2 HgCdTe-array with a pixel-size of 18 mu.